10 tháng 5 lúc 16:43

a: 5+2x=20-3x

=>2x+3x=20-5

=>5x=15

=>$x=\dfrac{15}{5}=3$

b: $7-\left(2x+4\right)=-\left(x+4\right)$

=>7-2x-4=-x-4

=>-2x+7=-x

=>-x=-7

=>x=7

c: $\left(5x+2\right)-3\left(2x+1\right)=-3x+7$

=>5x+2-6x-3=-3x+7

=>-3x+7=-x-1

=>-2x=-8

=>x=4

d: $2x-\left(3-5x\right)=4\left(x+3\right)$

=>2x-3+5x=4x+12

=>7x-3=4x+12

=>3x=15

=>$x=\dfrac{15}{3}=5$

e: $5\left(2x-3\right)-4\left(5x-7\right)=19-2\left(x+11\right)$

=>10x-15-20x+28=19-2x-22

=>-10x+13=-2x-3

=>-8x=-16

=>$x=\dfrac{-16}{-8}=2$

f: $x^2-\left(x+2\right)\left(x-2\right)=2x$

=>$x^2-\left(x^2-4\right)=2x$

=>2x=4

=>x=2

g: $\dfrac{1-3x}{6}+x-1=\dfrac{x+2}{2}$

=>$\dfrac{1-3x+6\left(x-1\right)}{6}=\dfrac{3\left(x+2\right)}{6}$

=>1-3x+6x-6=3x+6

=>3x-5=3x+6

=>-5=6(vô lý)

h: $\dfrac{3\left(2x+1\right)}{4}-5-\dfrac{3x+2}{10}=\dfrac{2\left(3x-1\right)}{5}$

=>$\dfrac{15\left(2x+1\right)}{20}-\dfrac{100}{20}-\dfrac{2\left(3x+2\right)}{20}=\dfrac{8\left(3x-1\right)}{20}$

=>30x+15-100-6x-4=24x-8

=>24x-89=24x-8

=>-89=-8(vô lý)

i: $\dfrac{2x+1}{3}-\dfrac{5x+1}{6}=\dfrac{x+1}{2}$

=>$\dfrac{2\left(2x+1\right)}{6}-\dfrac{5x+1}{6}=\dfrac{3x+3}{6}$

=>4x+2-5x-1=3x+3

=>3x+3=-x+1

=>4x=-2

=>x=-1/2

j: $\dfrac{3\left(x+3\right)}{4}+\dfrac{1}{2}=\dfrac{5x+9}{3}-\dfrac{7x-9}{4}$

=>$\dfrac{9\left(x+3\right)}{12}+\dfrac{6}{12}=\dfrac{4\left(5x+9\right)}{12}-\dfrac{3\left(7x-9\right)}{12}$

=>9x+27+6=20x+36-21x+27

=>9x+33=-x+63

=>10x=30

=>x=3

Bình luận (0)

Các câu hỏi tương tự
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết